Gender dalam Tinjauan Islam - Yoyoh Badriyyah (Lembaga Penerbitan dan Publikasi Ilmiah IAI Bunga Bangsa Cirebon, 2020)
Islam is a religion of empowerment, that is, a religion that requires the formation of the readiness and ability of each individual human being to carry out his role, namely to do good. Why is there an order in Islam to support the weak (dlo'if), look after orphans, and educate children? All of this is directed to the formation of mental and physical readiness to carry out his life existence. Thus, efforts to weaken, oppress, hegominate and tyrannize a person are things that Islam does not expect. The presence of gender as a marker of the existence of human genital variants - in Islamic views - is not something that needs to be contradicted. Both are just distinctions that have the same role and function, namely realizing divine values ​​(religion) which are true in accordance with His instructions (al-khoir) and the truth as a result of a just interpretation of the verses (al-ma'ruf). Thus, forms of injustice as a limitation effect of gender interpretations or interpretations of God's verses, are actually issues that need to be resolved. From this, the authors conclude that the gender movement as a form of movement to build justice and empowerment of men and women is not something that is against Islamic teachings but something that is in line with one of the teachings of Islam. Abstrak Islam adalah agama pemberdayaan yaitu agama yang menghendaki terbentuknya kesiapan dan kesanggupan tiap individu manusia untuk menjalankan perannya yaitu melakukan kebaikan. Mengapa di dalam islam ada perintah menyantuni orang lemah (dlo'if), memelihara anak yatim, dan mendidik anak-anak?. Semua ini diarahkan untuk terbentuknya kesiapan mental dan fisik untuk menjalankan eksistensi hidupnya. Dengan demikian, upaya-upaya pelemahan, penindasan, hegomoni dan tirani terhadap seseorang, menjadi hal yang tidak diharapkan oleh islam. Kehadiran gender sebagai penanda adanya varitas kelamin manusia –dalam tinjauan islam-bukanlah sesuatu yang perlu dipertentangan. Keduanya sekedar distingsi yang memiliki peran dan fungsi sama yaitu mewujudkan nilai-nilai ketuhanan (agama) yang kebenarnya sesuai dengan petunjuk-Nya (al-khoir) serta kebenaran sebagai hasil interpretasi berkeadilan ayat-ayatnya (al-ma'ruf). Dengan demikian, bentuk-bentuk ketidakadilan sebagai efek keterbatasan dari interpretasi gender atau hasil interpretasi terhadap ayat-ayat Tuhan, sesungguhnya persoalan yang perlu diselesaikan. Dari sinilah, penulis berkesimpulan bahwa gerakan gender sebagai bentuk gerakan membangun keadilan dan pemberdayaan kaum laki-kali dan perempuan, bukanlah sesuatu yang bertentangan dengan ajaran islam melainkan sesuatu yang selaras dengan salah satu ajaran islam.